Stigma Masyarakat terhadap Mantan Pengguna Narkoba di Kelurahan 24 Ilir Palembang - Muhammad Trysal (Jurnal Empirika, 2021)
Stigma is experienced by former drug users who live in Kelurahan 24 Ilir Palembang. The occurrence of stigma due to the views and responses given by the community to former drug users. The object of this research is the community residing in Village 24 Ilir Palembang that has met the criteria for determining informants. The purpose of this study was to find out and understand the stigma of society towards former drug users in Kelurahan 24 Ilir Palembang and was studied using the stigma theory from Erving Goffman. This research was conducted by qualitative method with qualitative descriptive type. The main informants in the study numbered eight people and the supporting informants were three people. The data collection techniques performed in this study are with in-depth interviews, observations and documentation. The results showed that stigma comes from people's assessment of former drug users in the environment, which is then interpreted by society to be stigmatised. In Kelurahan 24 Ilir Palembang there are former drug users who have varied ages and jobs, the factors that encourage drug use are divided into two, namely social and occupational environmental factors. While users who have stopped using drugs due to several factors such as having been rehabilitated, stopped on their own will or have a family. The stigma process that occurs in Kelurahan 24 Ilir Palembang starts from the association of former drug users to their environment, after which there is a public opinion about former drug users, then there is a stigma received by former drug users. The form of stigma in Kelurahan 24 Ilir Palembang is divided into four, namely former users feel blamed by the surrounding environment or feel viktimization, gossiped, ridiculed and a positive form that is given advice.